Reflection of Grain Yiefd Variability in Pearl millet on Biochemical Indicators of Soil Fertility - Kumar, Parveen; Manga, V K (Annals of Arid Zone, 2016)
Development of efficient N-utilizing genotypes can be an important strategy to increase pearl millet productivity in N-deficient soils of arid region. Therefore, 30 genotypes of pearl millet (Pellllisel/llll. glauculI1 (L) R. Sr.) were studied for determining the amountof genetic variability for NO,-N content and activity of nitrate reductase and dehydrogenase in the rhizosphere and their association with the grain yield. Significant variability existed among genotypes for these traits. Estimates of heritability in broad sense were high for all the traits. Genetic advance was high for NO,- ’. followed by nitrate reductase and dehydrogenase. Study revealed significantly high and positive association of grain yield with nitrate reductase and dehydrogenase, while it was negative between grain yield and NO,;-N. This suggested that high activity of nitrate reductase and dehydrogenase in the rhizosphere of pearl millet genotypes can be used alung with other yield component traits for improving pearl millet productivity in the nitrogen-deficient pwduction system of arid regions.